The advent of Amalivaca, a Guyanese legend Martí - Yanira Muñoz García; Alberto Iglesias Ortega (Revista MENDIVE, 2005)
This article begins with an analysis made by the Cuban essayist Cintio Vitier about the mythical figure of the Great Semí, which appears in a Venezuelan source that appears in the essay “Nuestra America”, written by José Martí, in his coincidences with Amalivaca and his expansion toward interpretations that relate him with a Guyanese legend where it is explained the genesis of this mythical figure, as well as his humanistic essence according to author's appreciations.